PENINGKATAN KREATIVITAS MENGGAMBAR DEKORATIF SISWA KELAS III MELALUI PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) - Ernawati, Fitri; Susiani, Tri Saptuti; Salimi, Moh (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
The study aimed to improve student’s creativity in decorative painting, and describe the constraints and solutions in the implementation of Contextual Teaching and Learning. It was classroom action research. The subjects were teacher and students of third grade at SDN 1 Mekarsari.  The data used is in the form of qualitative and quantitative data. Data collection techniques using tetst, observations, and interviews. Data validity uses triangulation of sources and techniques. Data analysis with data reduction, data presentation, and drawing conclusions. The results indicated that Contextual Teaching and Learning (CTL) improved student’s creativity in decorative painting. The students had interesting and unique ideas in painting. The student’s learning outcomes and works improved.  The constraints were the teacher had difficulty to manage the students when drawing and they needed much times to finish. The solutions were the teacher provided more efforts to manage the students. It concludes that the implementation of Contextual Teaching and Learning (CTL) improves creativity in decorative painting to third grade students